Mecanismos técnicos legales para formalizar territorios con valor ambiental según la Zonificación, Ecológica y Económica de San Martín - Silva Guerra, César Ulises (2010)
The present work is the application and proposal of a strategic analysis model for the registration and registration of land with high environmental value identified in the Ecological Zoning San Martin, based on work experience and binding enforcement sanitation Property state in the region and the country. Thus the present report summarizes a comprehensive analysis of the legislation exists for thecase and your linking it with the proposed Property Register as part of the final report. Likewise this thesis report contains a critical analysis of the different positions adopted state institutions when establishing mechanisms to safeguard common interests of the entire community in post conservation of natural resources. Meanwhile, common mechanisms between state institutions will be part of the development of plans and strategies to establish in our department seeking uniformity of processes which must include information and field verification information relating it to the legal case for which also presents basic elements of analysis and data collection. Moreover, taking into account the nature of the premises regarding application of research, these are located in the western sector of the Department, in the highest part of the Cordillera Oriental, bordering the Department of Liberty, Amazon and Huanuco.